Versatile Microwave-Assisted and Lanthanum Chloride Catalysed Synthesis of Polysubstituted Imidazoles Using Urea/Thiourea as Benign Source of Ammonia. Issue 4 (2012) - Manafi, Mohammad Reza; Manafi, Pedram; Kalaee, Mohammad Reza
Abstract : Lanthanum chloride was found to be an effective catalyst for the facile and one-pot synthesis of polysubstituted imidazoles under solvent free condition in excellent yields. This method elucidates urea/thiourea, as an environmentally benign source of ammonia for the synthesis of polysubstituted imidazoles. The work-up procedure is very simple and the products don't require further purification.